The Late Palaeozoic brachiopod genus Jakutoproductus Kashirtsev 1959 and the Jakutoproductus verchoyanicus zone, northern Yukon Territory, Canada - Guang Shi (1994)
The familial and subfamilial position, species composition, and geographic distribution of the Late Palaeozoic productid genus Jakutoproductus Kashirtsev 1959 are reviewed. Jakutoproductus is placed in the subfamily Plicatiferinae Muir-Wood & Cooper 1960 of the family Plicatiferidae. Eighteen described species from the Russian Arctic, Mongolia, northeast China, and northern Yukon Territory, Canada, are assigned to Jakutoproductus. The Jakutoproductus verchoyanicus Zone of late Sakmarian to Artinskian age, most likely early Artinskian (Aktastinian), here established is based on material from the Jungle Creek Formation, northern Yukon Territory, Canada, and is correlated with the following horizons in Russia: the Osennin Horizon in the Verchoyan Mountains, the lower Munugudjak Horizon of the Kolyma-Omolon Massif, the Hipkhoshin Suite of east Zabaikal, the lower Birrang Horizon of Taimyr, and an unnamed sandstone-shale unit on the north island of Novaya Zemlya.